Influences of product characteristics and process parameters on Vitamin C and color quality deteriorations in heat-treated grapefruit juice - Ables, Errol John O.
This study established predictive models for the individual and interactive influences of various combinations of process and product parameters namely, heating temperature, heating time, soluble solids (SS), and titratable acidity (TA) on the residual ascorbic acid (AA) content, and ascorbic acid loss (ΔAA) of simulated citrus juice (SCJ) systems using Response Surface Methodology (RSM). Polynomial models describing the individual and interactive influences of temperature, time, SS, and dilution rate on the Commission Internationale de l'Éclairage (CIE) color parameters of heat-treated grapefruit juice were also established using RSM. SCJs and grapefruit juice samples were prepared according to the combinations generated by the Central Composite Rotatable Design of Experiment. Only the individual linear effects of temperature and time significantly (P<0.05) affected AA and ΔAA. The individual linear and quadratic effects of SS and dilution rate significantly affected all CIE color parameters except for quadratic effects on a* and Δa* values. Furthermore, the linear influence of temperature on b*, Δb*, C*, and ΔC* were found to be significant; while CIE ΔE* values were significantly affected by the interactive influences of SS and dilution rate. All validating systems for the predictive models for AA and ΔAA had acceptable predictive efficacy with accuracy factor (Af) ranging from 1.00 to 1.60. On the other hand, mathematical validation of the resulting models for the CIE color parameters showed that 147 out of 180 (81.67%) systems were predicted within the acceptable margin of error. The results reported in this work may be useful in the establishment of specific heat process schedules for unique products, for the preservation of product quality.